1998
DOI: 10.1523/jneurosci.18-06-01970.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Domain of the Large Myelin-Associated Glycoprotein Isoform Is Needed for Proper CNS But Not Peripheral Nervous System Myelination

Abstract: The myelin-associated glycoprotein (MAG) is a member of the immunoglobulin gene superfamily and is thought to play a critical role in the interaction of myelinating glial cells with the axon. Myelin from mutant mice incapable of expressing MAG displays various subtle abnormalities in the CNS and degenerates with age in the peripheral nervous system (PNS). Two distinct isoforms, large MAG (L-MAG) and small MAG (S-MAG), are produced through the alternative splicing of the primary MAG transcript. The cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 51 publications
4
55
1
Order By: Relevance
“…The time course of myelination observed in the present study is consistent with the finding of a previous study using immunostaining for the major myelin components, including MBP, that myelin formation in the gray matter and the dorsal CST starts at around P11 in rats (Schwab and Schnell, 1989). Further, Western blot studies have shown that MAG expression dramatically increases after P14 (Fujita et al, 1998;Cho et al, 2005). Our results on MAG expression are also consistent with those of the MAG mRNA expression reported previously (Jordan et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…The time course of myelination observed in the present study is consistent with the finding of a previous study using immunostaining for the major myelin components, including MBP, that myelin formation in the gray matter and the dorsal CST starts at around P11 in rats (Schwab and Schnell, 1989). Further, Western blot studies have shown that MAG expression dramatically increases after P14 (Fujita et al, 1998;Cho et al, 2005). Our results on MAG expression are also consistent with those of the MAG mRNA expression reported previously (Jordan et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…As another sensitive marker of oligodendrocyte maturation, we determined the S-MAG/L-MAG mRNA ratio by RT-PCR. These two MAG variants are produced by alternative splicing and their ratio increases during oligodendrocyte differentiation (Fujita et al, 1998). No significant differences in the S-MAG/L-MAG ratio at P10 or P28 were detected between the three genotypes examined (Fig.…”
Section: Normal Oligodendrocyte Differentiation In Fa2hmentioning
confidence: 87%
“…The processes of central and peripheral axonal myelination are accomplished by partially distinct mechanisms Fujita et al, 1998). The myelinating cells of the CNS and PNS are distinct, with each oligodendrocyte myelinating multiple axonal internodes in the CNS, but Schwann cells providing myelination for a single peripheral axonal internode.…”
Section: Central Vs Peripheral Myelinationmentioning
confidence: 99%